Approximation of continuously Gâteaux derivable functionals by Markov operators - S. G. Gal (Journal of Numerical Analysis and Approximation Theory, 1996)
The main purpose of this paper is to extend a classical quantitative result in approximation of continuously derivable functions on [a, b] by positive and linear operators, to the approximation by Markov operators of the real-valued functions defined and having a continuous Gateaux derivative on a compact convex subset of a normed space.